How do climate change and associated hazards impact on the resilience of riparian rural communities in Bangladesh? : policy implications for livelihood development - G. M. Monirul Alam and Khorshed Alam and Shahbaz Mushtaq and Walter Leal Filho (Environmental Science & Policy, 2018)
Despite the increasing recognition of the need for building resilience among poor farmers in developing countries in the face of changing climate conditions, there is a lack of information on the various factors influencing their resilience capacity. This paper develops an indicator-based Resilience Capacity Index (RCI) aimed at a better understanding of the factors influencing resilience capacity of the most hazard-prone riparian rural households in Bangladesh, as a case study in a developing country. The RCI is a relative measure and the value ranges between 0 and 1, where the higher the value the higher the resilience capacity. The index value of 0.297 for riverine mainland households is significantly higher than that for char (island) households (0.201). However, the lower index values in both locations infers the households’ inability to cope with and adapt to the impacts of climate change and associated hazards due to a lack of adaptation options along with their poor socio-economic conditions. The main drivers of the resilience capacity include livelihood strategies, level of education, and access to food, water and health services. Creating employment opportunities, increasing the level of education, and ensuring access to food, water and health services are potential climate-resilient strategies that are likely to enhance the resilience capacity of most vulnerable riparian households across Bangladesh, with some experiences which may be replicable elsewhere.
Keywords: Bangladesh; Climate change; Resilience capacity index (RCI); Rural households; Vulnerability